Synthesis, characterization and oxidation of metallic cobalt (Co) thin film into semiconducting cobalt oxide (Co3O4)thin film using microwave plasma CVD. (1st June 2018) - Ansari, Akhalakur Rahman; Hussain, Shahir; Imran, Mohd; Abdel-wahab, M Sh; Alshahrie, Ahmed
Abstract: The pure cobalt thin film was deposited on the glass substrate by using DC magnetron sputtering and then exposed to microwave assist oxygen plasma generated in microwave plasma CVD. The oxidation process of Co thin film into Co3 O4 thin films with different microwave power and temperature were studied. The influences of microwave power, temperature and irradiation time were investigated on the morphology and particle size of oxide thin films. The crystal structure, chemical conformation, morphologies and optical properties of oxidized Co thin films (Co3 O4 ) were studied by using x-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM), Raman Spectroscopy and UV–vis Spectroscopy. The data of these films showed complete oxidation pure metallic cobalt (Co) into cobalt oxide (Co3 O4 ). The optical properties were studied for calculating the direct band gaps which ranges from 1.35 to 1.8 eV.